Factors Influencing Teachers' Acceptance of Using Google Classroom in Mathematics Blended Learning - Nazri, Sedi; Mohammad Nur Azhar, Mazlan (Universiti Pendidikan Sultan Idris, 2023)
This concept paper will discuss the definition and concept of Blended learning in Mathematics as well as the factors of teachers' acceptance of using Google Classroom in Mathematics Blended Learning based on previous technology acceptance models. The factors of teachers' acceptance of using Google Classroom in Mathematics Blended Learning have been identified through the extensive analysis of the previous literature review. The purpose of this concept paper is to discuss in detail the design and selection of the acceptance factors of teachers using Google Classroom in Mathematics Blended Learning. This concept paper is expected to give a complete picture related to the factors that influence teachers' acceptance of using Google Classroom, especially in Mathematics Blended Learning and serve as a guide to stakeholders and policy implementers to take the initiative to use Google Classroom in the field of Mathematics education in Malaysia a success.